Intervensi Non Farmakologi untuk Meningkatkan Kualitas Tidur Postpartum: Kajian Literatur - Ratrika Sari; Anggorowati Anggorowati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: Post-partum mothers experience an inadequate sleep quality, either because of new roles or changes during postpartum. The use of drugs in the postpartum period requires consideration because it is risky for both mother and baby, so non-pharmacological interventions are safer alternative choices. During the postpartum period, the mother also carries out her own care so that non-pharmacological interventions are needed because they can be doing by self. This literature review aims to know the types of non-pharmacological interventions to improve the sleep quality of postpartum mothers. Methods: This literature review search uses the database of Science Direct, PubMed, Google Scholar, EBSCO using the keywords